Synthesis of gold(iii) ← gold(i)–NHC through disproportionation: the role of gold(i)–NHC in the induction of apoptosis in HepG2 cells. (18th May 2016) - Nandy, Abhishek; Samanta, Tapastaru; Mallick, Sumana; Mitra, Partha; Seth, Saikat Kumar; Saha, Krishna Das; Al-Deyab, Salem S.; Dinda, Joydev
Abstract : The anticancer activities of novel Au(i ) and Au(iii )–NHC complexes based on 2-[(6-methylpyridin-2-yl)]imidazo[1, 5- a ]pyridin-4-ylium hexafluorophosphate have been investigated. Abstract : Starting from the proligand 2-[(6-methylpyridin-2-yl)]imidazo[1, 5- a ]pyridin-4-ylium hexafluorophosphate(1 ·PF6 ), three new complexes, viz. [Au(1)2 ] [PF6 ] (2 ), [1/2AuCl2, 1/2AuCl4 ] − [(1H)] + (3 ), and [Au(1)Cl3 ] (4 ), have been synthesized and characterized employing different spectroscopic methods. [Au(1)Cl3 ] (4 ) has been synthesized by the disproportionation process. During the transformation of2 to4, the annelated proligand stabilizes both Au(i ) and Au(iii ), and the isolation of the intermediate (3 ) confirms the conversion of Au(i ) → Au(iii ) through the disproportionation pathway. The solid state structures of2, 3 and4 have been determined. Linear geometry was observed in2, whereas complex4 adopted square-planar geometry. Gold complexes2 and4 have been subjected to growth inhibitory studies. Complex2 induced apoptosis in HepG2 cells along with increased expression of proteins involved in the mitochondrial death pathway, suggesting that apoptosis may occur via the mitochondrial death pathway.